Rational, Pragmatic and Competitive: Generation “Y” Stereotype Empiric Research - Rikel A.M. (Социальная психология и общество, 2020)
Objectives. The study of the socio-psychological portrait of the so-called “Y” generation (born 1982—1999) in terms of stereotypes and autostereotypes regarding the rationality and pragmatism of this generation. Background. Stereotypes that arise when interacting with people of another generation, always remain a relevant topic due to the constant change of generational cohorts. The media and popular image of the “Y” generation in the context of its rationality and pragmatism is due to the socialization of most representatives of this generation in the new post-Soviet individualized and “market” Russian society. Study design. The study was carried out in 3 stages and was based on a mixed qualitative and quantitative methodology (which may explain the limited sample size). Participants. 100 people (Stage I — 62, II — 18, III — 20), representatives of the so-called generations “Y” and “X” (Russia). Methods. At Stage I, a questionnaire survey and an author’s projective method were used, dedicated to the perception of interpersonal relations in movies; at Stage II — an in-depth interview on the topic of romantic relationship; at Stage III — a semi-structured interview on the topic of organizational loyalty. Results. Data were obtained according to which the generation “Y” perceives itself, as well as is perceived by the older generation “X” as (1) more rational in romantic relations, (2) different in terms of interpreting the presence of competition and cooperation in interpersonal relations, and as well as (3) a less loyal and more pragmatic in terms of organizational career generation. Conclusions. The obtained results confirm the stereotypes of the “Y” generation that have developed in the media space considered in the article, and also contribute to the formation of a comprehensive socio-psychological portrait of representatives of this generational cohort.